If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3(2x-6)=2(x-3)
We move all terms to the left:
3(2x-6)-(2(x-3))=0
We multiply parentheses
6x-(2(x-3))-18=0
We calculate terms in parentheses: -(2(x-3)), so:We get rid of parentheses
2(x-3)
We multiply parentheses
2x-6
Back to the equation:
-(2x-6)
6x-2x+6-18=0
We add all the numbers together, and all the variables
4x-12=0
We move all terms containing x to the left, all other terms to the right
4x=12
x=12/4
x=3
| 4x-0,01x^2=120 | | 3(v−5)=6 | | 12-0,8y=26+0,6y | | 15x+100=20x+50 | | 24=(h/2)-14 | | 12n+8–5n=42. | | 15x-11-13x=3 | | 12-0,8y=26+0, | | 23/5=10/11p | | X+x-13+x=x+25 | | 4s=3/5 | | 2=10-v | | 2=10−v | | 8-y-4(2-3y)=24+3y | | 4+x=x+3 | | 1/5u=43/4 | | (x+4)/2=19 | | 3.33=9n | | 25e+8-18=15 | | 0,5y-14=-29+0,8y | | n+3/3=2 | | 5x-5+2x+6=-6 | | x/90-1/9=1/9 | | 368=-3x-7(-8+7x) | | X/8-4=0-0,4x+9=0 | | a/8-6=18 | | 69=2x-3+69 | | -3w-4=w3 | | 168=4(2-5x) | | 3y=7-1 | | x/3+8=-10 | | -6(1+8x)=330 |